Chlamydia infection, PID, and infertility: further evidence from a case-control study in China - Lijun Liu; Changchang Li; Xuewan Sun; Jie Liu; Hepeng Zheng; Bin Yang; Weiming Tang; Cheng Wang (BMC, 2022)
Abstract Background Chlamydia trachomatis infection and pelvic inflammatory disease (PID) are well-known risk factors for female infertility. But there is limited evidence from China. This study aimed to further explore the associations between previous/current chlamydial infection, PID, and infertility in China. Methods We performed a 1:2 matched case-control study with two control groups: pregnant controls and non-pregnant controls in China in 2019. Women diagnosed with infertility were selected as cases (n = 255). Controls were selected based on the following criteria: Pregnant women who were documented in the selected hospitals were chosen as Pregnant controls (n = 510), and people who sought health care in Obstetric/Gynecologic clinics, Family Planning clinics, Dermatology and STD Department or Urological department were selected as Non-pregnant controls (n = 510). Infertility induced by male factors and people who used antibiotics in the vagina within two weeks were excluded. The first-stream specimen of urine samples was tested for chlamydia by nucleic acid amplification testing (NAAT). Conditional logistic regression was used to estimate the association. Results The prevalence of previous chlamydial infection and PID were significantly higher in cases (2.4%, 17.3%) than in controls (Non-pregnancy: 0.4%, 3.0%; Pregnancy: 0.4%, 9.0%). The current chlamydial infection rates were 5.9%, 7.3%, and 7.1% in infertile, pregnant, and non-pregnant women, respectively. After adjusting for confounders, PID largely elevated the risk of infertility (using non-pregnant controls: adjusted OR = 2.57, 95% CI 1.51, 4.39; using pregnant controls: adjusted OR = 6.83, 95% CI 3.47, 13.43). And the positive association between PID and tubal infertility was more obvious for both groups. For current chlamydial infection, none of the odds ratios were significant at the 0.05 level, while small sample size limited the evaluation of an association between prior chlamydial infection with infertility. Conclusions Previous PID was indicated to largely increase the risk of infertility, especially tubal infertility. And there should be continuing emphasis on highly sensitive and specific biomarker for prior chlamydial infection.